Comparison of Proportional Integral Derivative and Fuzzy Logic Controllers: A Literature Review on the Best Method for Controlling Direct Current Motor Speed - Putra, Agus Mulya; Maradona, Hendri; Rohmah, Rina Ari (International Journal of Robotics and Control Systems, 2025)
Control systems, particularly for DC motors, are a continually evolving field with various methods and techniques aimed at improving control system performance. Common issues in DC motor control, such as high overshoot and inadequate response times, highlight the need for further research into more effective tuning techniques. This study compares conventional PID and FLC methods in controlling DC motor speed, while also exploring optimization potential through new approaches like hybrid methods and the use of neural networks. The contributions of this research include a comprehensive analysis of previous studies on DC motor control performance and an in-depth assessment of the effectiveness of PID and FLC methods in addressing rise time, settling time, and overshoot issues. The methodology used in this study is a literature review, which involves collecting and analyzing various studies related to the application of both methods in DC motor control. Literature selection criteria include relevance, methodology used, and contributions to scientific advancements in motor control. The analysis shows that FLC performs better in handling overshoot, with previous studies indicating its ability to completely eliminate overshoot. Although the PID method is simpler and easier to apply in systems with linear characteristics, FLC offers better flexibility and adaptability for managing uncertainty and non-linear systems. Recommendations for further research are also presented, including a deeper exploration of integrating the two methods in a hybrid control system to enhance motor control performance.